Integration of structural information within a BIM-based environment for seismic structural e-permits - Ciccone, Angelo; Ciotta, Vittoria; Asprone, Domenico (Journal of Civil Engineering and Management, 2023)
The assessment of the structural safety of buildings, with the related outcomes and other structural information, is typically reported in un-structured sets of documents (tables, drawings, reports, etc.). This happens even if Building Information Modelling (BIM) workflows, platforms, and standards are adopted. Generally, the BIM database provides input data for the structural design, but most of the data produced by structural designers, according to the structural codes, do not fully integrate into the BIM database along with other context-related information. These data are not easily recorded, especially in openBIM standard file formats such as Industry Foundation Classes (IFC). In the context of digital procedures for permit applications pertaining to seismic structural engineering, the authors propose an openBIM approach for the integration of structural information to support the activities of building authorities’ bodies (BABs). The proposed framework has led to the development of an Information Delivery Manual (IDM) and a Model View Definition (MVD), considering the IFC schema, for the integration and exchange of information within a BIM-based environment. Successively, the authors implemented the proposed IDM/MVD solution in a case study that provided an effective workflow for innovative future delivery of necessary information to building authorities to obtain seismic authorization permits.